Das provas no processo previdenciário - Laurindo, Ailton Aparecido (2006)
This current paper has as its main purpose to approach the matter of evidences on the social security proceedings, under a practical and theoretical perspective, in agreement with jurisprudence and its due legal process. This actual theme has been chosen due to the fact that I have worked with social security practice for several years as a public employee, and also together with the studies on material social security. The choice is also justified with the purpose of a reinterpretation or a change in the legislature concerning social security proceeding rules, which are at a perceptible state of retrocession, harnessed into those old precepts, despite having being prepared after the publication of the present Constitution. In short, after some brief considerations regarding the conception about Social Security, Social Welfare, Health and Social Security, as well as the various forms of Social Security benefits, the paper will investigate the applied evidences on the social security proceedings, among which, documentary evidence, testimonial evidence, expert evidence, administrative justification and evidence to prove economical dependency and to prove performed activities under special conditions, all in agreement with jurisprudence and its due procedural legislation. In this context, several problems on the social security procedural legislation will be examined all with its due legal proceedings and with the basic rules based on the Code of Civil Procedure. Finally, some important conclusions obtained during this present study, which confirm the necessity for a change on the jural-social security legal system in such a way that its proceeding rules (clearly expressed or implied) are interpreted and applied in favour of the weakest part on the jural-procedural relation, in casu, the insured